Benefits of using Internet of Things technology for fuel management at a mechanised underground platinum bord and pillar mine: A Bathopele mine case study - Thema, Sephela Makete (University of the Witwatersrand, Johannesburg, 2024)
The advent of the fourth industrial revolution, Environmental Social and Governance (ESG), and push for green energy transition has propelled mining companies to reconsider their strategies. Over the past two decades, mining companies along the Bushveld Igneous complex in South Africa have been shifting towards mechanized mining methods which are generally safer and provide for the generation of greater volumes of output. Sibanye Stillwater’s Bathopele mine, which has a fleet of over two hundred and fifty (250) trackless mobile machinery (TMM) and a daily fuel consumption of approximately ten thousand (10 000) liters per day. The introduction of Internet of Things (IOT) technology in the fuel management system at Bathopele mine achieved benefits such as fuel consumption tracking, effective inventory management, prevention of fuel theft, detection of fuel leaks, determination of maintenance requirements and readily available access to fuel use data. This access to data enabled the mine to effectively apply for fuel use rebates from the South African Revenue Services (SARS) with ease. To determine the impact of the increased distance to underground working places on the refueling of TMM, the Theory of Constraints (TOC) method, qualitative and quantitative techniques were applied. A bivariate analysis conducted indicated a linear relationship between fuel consumption and production output at Bathopele mine, which suggests that an effective fuel management system had a positive impact on production output at the mine. A real-time or near real time model for fuel management in underground trackless bord and pillar mines in proposed.
A dissertation submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Engineering, in the School of Mining Engineering, in 2024.
Keywords: Internet of Things (IOT); Fuel Management; Fourth Industrial Revolution; Refueling; Trackless Mobile Machinery; Production activities; Environmental Social and Governance (ESG); Trackless Mobile Machinery (TMM); UCTD; SDG-17: Partnerships for the goals